Optimization of 3D printing parameters for strength enhancement of PLA notched curved panels using Taguchi method - Abdul Jalil, Abdul Malik Hussein; Kuntjoro, Wahyu; Mohd Nasir, Rizal Effendy; Saedon, Juri (UiTM Press, 2026)
Prototypes and components are increasingly printed using 3D printing. 3D printing issues depend on component shape and material. How 3D printing is done always affects structural component properties. Contemporary structural components, especially in small, unmanned planes, use 3D-printed curved panels with notches. This paper optimised 3D printing parameters to find the strongest notched curve panel using the Taguchi experimental design. PLA was used. The method involved 3D printing notched curve specimens with dimensions of 200 × 80 × 1.8 mm and a fixed notch diameter of 40 mm. Notched panel curve radius is 800 mm. Creality CR10S Pro-V2 3D printer printed the specimens. Three specimens were created for each configuration, utilising 3D printing parameters: printing direction, nozzle temperature, printing speed, layer thickness, and infill percentage, which were identified through literature reviews. The specimens were tested for strength using the universal testing equipment after printing. After collecting test data, the Taguchi design of experiment was used to determine the best process parameters. Specimen with configuration number five (5), printing direction 90, nozzle temperature 195 C, printing speed 60 mm/s, layer thickness 0.2 mm, and infill percentage 100%, produced the highest strength. Analysis of variance (ANOVA) and S/N ratio response validated this conclusion. The formula ‘larger-the-better’ showed that printing direction had the highest S/N Ratio (8.2659). Printing direction, nozzle temperature, and speed contributed 55%, 27%, and 8%, respectively, to the process optimisation, according to ANOVA. Taguchi design of experiment can optimise the 3D printed notched curve shell for strength.